TLR9 activation is required for cytotoxic response elicited by baculovirus capsid display - Molinari, Maria Paula; Crespo, Maria Ines; Molina, Guido Nicolas; Dho, Nicolás D.; Marinho, Fábio V.; Maletto, Belkys Angélica; Leclerc, Claude; Oliveira, Sergio C.; Taboga, Oscar Alberto; Cebrian, Ignacio; Moron, Victor Gabriel (Wiley, 2023)
Although the baculovirus Autographa californica multiple nuclear polyhedrosis virus (AcMNPV) infects lepidopteran invertebrates as natural hosts, represents an efficient vector for vaccine development. Baculovirus surface display induces strong humoral responses against viruses and parasites. A novel strategy based on capsid display carrying foreign antigens in the AcMNPV particle further improved the immune response by eliciting CD8+ T cell activation. In this study, we analyze the intracellular mechanisms and signalling pathways involved in CD8+ T cell activation by capsid display. Our results show that baculovirus can attach to the cell surface, enter dendritic cells (DCs), transit within endocytic vesicles and escape to the cytosol for further degradation by the proteasome. We found that the availability of viral proteins, endosomal acidification, and proteasome activity are needed for efficient Major Histocompatibility Complex class-I presentation by baculovirus carrying Ovalbumin in the viral capsid. Importantly, we demonstrated with this strategy that the induction of cytotoxic T cells and IL-12 production by DCs are TLR9-dependent and STING-independent. Finally, our study shows differential intracellular processing for capsid and surface baculovirus proteins in DCs and highlights the role of different danger receptors during cytotoxic T cell priming through the capsid display delivery system, which could lead to improved baculovirus-based vaccines development.